2016
DOI: 10.1007/s10067-016-3435-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of biologics for the management of rheumatoid arthritis: systematic review and network meta-analysis

Abstract: Our aim was to establish the comparative effectiveness of rheumatoid arthritis (RA) biologics, using a systematic review and network meta-analysis. The systematic review used randomized controlled trials (RCTs) in adults with RA who failed treatment with conventional disease-modifying agents for rheumatoid disease (cDMARDs). We compared the effectiveness of abatacept, adalimumab, etanercept, infliximab, certolizumab pegol, golimumab, and rituximab to tocilizumab, a recent biologic with a different mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 16 publications
1
20
0
3
Order By: Relevance
“…Initiating treatment, aiming for sustained remission or low disease activity early in the course of the disease, is important to preserve physical function and improve long-term prognosis [ 5 7 ]. Biological disease-modifying anti-rheumatic drugs (DMARDs) are to date mainly used as the second line of therapy in the management of early RA, although several studies showed their superior efficacy over traditional DMARDs in reducing disease activity and halting joint damage [ 8 , 9 ]. Starting biological therapy in newly diagnosed RA patients as standard care, however, still remains highly controversial considering costs and unnecessary exposure to adverse events as a proportion of patients will be over-treated when using such an approach.…”
Section: Introductionmentioning
confidence: 99%
“…Initiating treatment, aiming for sustained remission or low disease activity early in the course of the disease, is important to preserve physical function and improve long-term prognosis [ 5 7 ]. Biological disease-modifying anti-rheumatic drugs (DMARDs) are to date mainly used as the second line of therapy in the management of early RA, although several studies showed their superior efficacy over traditional DMARDs in reducing disease activity and halting joint damage [ 8 , 9 ]. Starting biological therapy in newly diagnosed RA patients as standard care, however, still remains highly controversial considering costs and unnecessary exposure to adverse events as a proportion of patients will be over-treated when using such an approach.…”
Section: Introductionmentioning
confidence: 99%
“…18 These newer therapeutic targets have complex and variable effects on T-cell activation, and current therapeutics aimed at any one of these targets have varying interactions with the inflammatory environment, highlighting the urgency to develop tools to both investigate relationships of immune-modulating networks in vivo and monitor the immune-based effects of therapy in patients. 19-26 …”
Section: Introductionmentioning
confidence: 99%
“…[4]. В одном из мета-анализов [5] выявлено преимущество тоцилизумаба перед другими БЛС. Однако судить о преимуществах одного БЛС перед другими сложно ввиду ничтожно малого количества прямых «голова к голове» исследований эффективности БЛС между собой.…”
Section: Introductionunclassified
“…После связывания с ритуксимабом, В-клетки погибают вследствие запуска ряда механизмов, включающих антитело-зависимую клеточно-опосредованную цитотоксичность, комплемент-зависимую цитотоксичность и апоптоз [7]. При изучении возможных предикторов ответа на анти-В-клеточную терапию установлена хорошая эффективность ритуксимаба при серопозитивном РА, при значительном повышении АЦЦП и РФ (больше трех верхних границ норм) [5]. Положительный эффект анти-В-клеточной терапии ритуксимабом наблюдался у пациентов с васкулитом, кератитом, склеритом, легочными узелками и синдромом Фелти [8][9][10].…”
Section: Introductionunclassified